The Use of Inquiry-Based Handouts on Science Learning for Student Critical Thinking Ability - Suparmi, Suparmi; Yustina, Yustina; Syafii, Wan (FKIP-Universitas Riau, 2019)
The problem that is often found in the field is that poorly trained students thinking critically because learning is still teacher-centered. The purpose of this study was to determine the effect of using inquiry-based handouts on students critical thinking abilities. The design of this study was experimental design with pretest and posttest group control design methods. It was by looking at the students ability to answer the pretest and posttest question sheets that contain critical thinking indicators such as analyzing, synthesizing, connecting, concluding, evaluating, and creating. The results of this study show that the students critical thinking skills for the group given the handout showed that they met good criteria, that is the average score above 75. Meanwhile, students critical thinking skills in the class or group of students who were not given handouts were still not more than 50. From the results of the study it can be concluded that the handouts used can help students in training critical thinking skills.